Molecular evidence of Wolbachia in bat-associated mite Periglischrus Iheringi Oudemans, 1902 (Mesostigmata: Spinturnicidae) from Brazil - Bassini-Silva, Ricardo; Calchi, Ana Cláudia [UNESP]; Castro-Santiago, Ana Carolina; Marocco, João Carlos; Dorigoni, Letícia; de Quadros, Rosiléia Marinho; André, Marcos Rogério [UNESP]; Barros-Battesti, Darci Moraes [UNESP]; Dowling, Ashley P. G.; Labruna, Marcelo Bahia; Jacinavicius, Fernando de Castro (Springer Nature, 2025)
Wolbachia is an intracellular endosymbiont bacterium found in nematodes and arthopods. Regarding mites, the Wolbachia supergroup U has been described based on strains found in the genus Spinturnix. In this study, ten specimens of Periglischrus iheringi (Mesostigmata: Spinturnicidae), collected from Artibeus obscurus (Chiroptera: Phyllostomidae) in Santa Catarina State, were found to be infected with Wolbachia. Phylogenetic analysis based on the 16 S rRNA gene revealed that the detected Wolbachia strain belongs to Supergroup F, which has also been detected in other ectoparasitic arthropods, such as Columbicola columbae (slender pigeon lice) and Cimex lectularius (bed bug). This study presents the first molecular detection of Wolbachia in P. iheringi.
Keywords: 16S rRNA; Artibeusspp; Ectoparasite; Endosymbionts; Supergroup F; Wing mite